Advances in PIWI-piRNA function in female reproduction in mammals - Lv Xiaolong; Zhang Hongdao; Wu Ligang (Acta Biochimica et Biophysica Sinica)
PIWI-interacting RNAs (piRNAs), which associate with PIWI clade Argonaute proteins to form piRNA-induced silencing complexes (piRISCs) in germline cells, are responsible for maintaining genomic integrity and reproductive function through transcriptional or post-transcriptional suppression of transposable elements and regulation of protein-coding genes. Recent discoveries of crucial PIWI-piRNA functions in oogenesis and embryogenesis in golden hamsters suggest an indispensable role in female fertility that has been obscured in the predominant mouse model of PIWI-piRNA pathway regulation. In particular, studies of piRNA expression dynamics, functional redundancies, and compositional variations across mammal species have advanced our understanding of piRNA functions in male and, especially, female reproduction. These findings further support the use of hamsters as a more representative model of piRNA biology in mammals. In addition to discussing these new perspectives, the current review also covers emerging directions for piRNA research, its implications for female fertility, and our fundamental understanding of reproductive mechanisms.